Inhibitory Mechanism of Robiotic Bacteria on The Growth of Vibrio harveyi in Tiger Shrimp (Penaeus monodon) Larvae - . Widanarni; E. Ayuzar; . Sukenda (Jurnal Akuakultur Indonesia)
Three probiotics named SKT-b, 1Ub, and Ua had inhibitory activity against the growth of Vibrio harveyi. These strains were mutated by rifampicin resistant. The inhibitory effect of SKT-b,1Ub, and Ua on the growth of V. harveyi was investigated by concomitant incubation of the two bacteria in a culture shrimp larvae. Colony forming unit of V. harveyi, probiotic and total of bacteria in dead, live larvae and water culture was monitored, and survival rate of larvae was investigated. Shrimp inoculated probiotic previously had survival rate higher than control (without probiotic). Number of V. harveyi in treatment without probiotic inoculation also higher compared to treatment with probiotic inoculation in dead, live larvae and water culture.  It demonstrated possible inhibition of probiotic bacteria on V. harveyi through competition for adherence sites or nutrition source. Partial sequencing of 16S-rRNA gene showed that 1Ub was similar to Pseudoalteromonas piscicida, whereas SKT-b and Ua were similar to Vibrio alginolyticus.